Event‐switched control design with guaranteed performances - Boisseau, Bruno; Martinez, John Jairo; Raharijaona, Thibaut; Durand, Sylvain; Marchand, Nicolas (International journal of robust and nonlinear control, 2017)
Summary In this paper, a new event‐switched control method is presented for controlling discrete‐time linear systems subject to bounded disturbances. The main advantage of the proposed method is that the nominal performance of the controlled system with periodic control updates is kept in a framework that do not require to periodically update the control law. The feedback control loop can be opened as long a state‐dependent event condition is satisfied. This condition is obtained using set theory approaches. In particular, the concept of robustly positively invariant sets is used to calculate the nominal performance and the event condition. The simulation presented in this paper confirms the efficiency of the present approach. A reduction of the numerical complexity of the approach is also proposed. Copyright © 2016 John Wiley & Sons, Ltd.